2012
DOI: 10.4082/kjfm.2012.33.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Cholesterol Level and Bone Mineral Density at Lumbar Spine and Femur Neck in Postmenopausal Korean Women

Abstract: BackgroundBlood lipid profiles have been suggested to be a risk factor for osteoporosis. However, the association between lipid profiles and bone mineral density (BMD) is still unclear. This study aimed to evaluate an association between blood lipid profiles and BMD through both a cross-sectional and a longitudinal study.MethodsStudy subjects were 958 postmenopausal Korean women who have repeatedly undertaken laboratory tests and BMD measurements at lumbar spine and femur neck with an interval of 7.1 years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Go et al . likewise found no significant variations in the spinal or femoral BMD as a result of changes in LDL cholesterol levels in 958 postmenopausal women after a follow‐up period of 7 years . In fact, Tanko et al .…”
Section: Discussionmentioning
confidence: 90%
“…Go et al . likewise found no significant variations in the spinal or femoral BMD as a result of changes in LDL cholesterol levels in 958 postmenopausal women after a follow‐up period of 7 years . In fact, Tanko et al .…”
Section: Discussionmentioning
confidence: 90%
“…Some studies suggest that dyslipidemia could result in both increased bone resorption and decreased bone formation [1]. Various studies have tried to evaluate the association between lipid level and osteoporosis, but the results were proved to be controversial [1][2][3][4][5][6][7]. Some studies found an inverse relationship with bone mineral density (BMD) [1][2][3][4][5], whereas others have shown a positive correlation [6] or no correlation [7].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies showed no effect of dislipidemia on BMD [27][28][29][30], others reported that there is either a negative [31][32][33][34][35] or a positive effect [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Jeong-Ho Go et al in 2012 found no association between serum lipids and BMD in postmenopausal Korean women [28].…”
Section: Introductionmentioning
confidence: 99%